1975
DOI: 10.1128/jb.123.2.642-650.1975
|View full text |Cite
|
Sign up to set email alerts
|

Physical and chemical studies of Thiobacillus ferroxidans lipopolysaccharides

Abstract: The lipopolysaccharides (LPS) of the obligate acidophile Thiobacillus ferrooxidans grown on iron, sulfur, and glucose as energy sources were examined for various physical and chemical properties. Both qualitative and quantitative variations were found among the three preparations. The LPS extracted from iron-grown cells (Fe-LPS) contained less than 3% protein compared to 18 to 25%c in LPS extracted from either sulfur-grown cells (S-LPS) or glucose-grown cells (G-LPS). S-LPS showed two distinct sedimentable spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Bands that stained yellow contained carbohydrate, while bands that stained blue were predominantly proteinaceous. Other laboratories have reported that the lipopolysaccharides of T. ferrooxidans grown on soluble ferrous ions or sulfur are chemically different (13,31) or identical (34) for different strains. The difference in banding patterns in Fig.…”
Section: And Discussionmentioning
confidence: 99%
“…Bands that stained yellow contained carbohydrate, while bands that stained blue were predominantly proteinaceous. Other laboratories have reported that the lipopolysaccharides of T. ferrooxidans grown on soluble ferrous ions or sulfur are chemically different (13,31) or identical (34) for different strains. The difference in banding patterns in Fig.…”
Section: And Discussionmentioning
confidence: 99%
“…In turn, the proteins of the outer membrane are strongly influenced by the conditions of growth (1, 3, 18); e.g., growth phase, carbon source, and catabolite repression change the composition of the major protein group in the E. coli outer membrane (18). Also, the LPS composition changes in different culture media (11,17). In the relationship presented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased yield of cyclopropane fatty acids in bacterial lipid preparations formed with acid hydrolysis has been known for a long time [30]. A methoxy fatty acid has been defined by GC/MS in the lipopolysaccharide-lipid A of Thiobacillusferrooxidans [31]. It was this paper that encouraged us to examine the lipids of other Thiobacillus spp., using the mild alkaline methanolysis procedure, for signature PLFA that could be utilized in environmental studies.…”
Section: Structural Identification Of Unusual I'li-'a Frommentioning
confidence: 99%